Investigation of Flow Turbulence in the Ring Channel with Cyclone Whirling Generator - Y. L. Leukhin; E. N. Sabourov; A. S. Skachkov; V. Garen; S. Tideken (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper gives and analyses the results of experimental investigations of turbulent intensity of whirled flow in the ring channel with cyclone whirling generator. The investigations have been carried out with the help of a laser Doppler’s anemometer with the following values of the Reynold’s number Re = 770... 10,9 ∙ 10.